KERAGAMAN GENETIK TANAMAN JARAK PAGAR (Jatropha curcas L.) AKSESI UNGGUL HASIL PERSILANGAN BERBASIS RAPD (RANDOM AMPLIFIED POLYMORPHIC DNA) - Baiq Muli Harisanti (Lembaga Penelitian dan Pendidikan Mandala, 2016)
The use of genetic diversity for the study of kinship between two individuals or two populations within a species is necessary documented. This study aimed to analyze the genetic diversity of Jatropha (Jatropha curcas L.) by using RAPD. This type of research is descriptive developmental research. This study was to analyze the genotypic diversity of crossbred various accessions of Jatropha (Jatropha curcas. L) with RAPD technique. The study population was the whole Jatropha (Jatropha curcas L.) accessions superior results of a cross contained in District Kalipare, Kediri. The sample in this study is jatropha (Jatropha curcas L.) the result of crossing the winning numbers covering 4 numbers of crossbred plants originating from Kalipare, East Java. Based on the analysis of kinship based RAPD embodied in dendogram of Jatropha (Jatropha curcas L.) crosses the superior results indicate that the accession to the elders SM 35 X SP 38 and SP 8 X SP 38 have smaller level of genetic similarity, namely 56 , 8% compared with the level of genetic similarity among accessions with elders SP HS 33 X 8 X 49 and SP 16 SP 76,3%. If traced the origin of the elders of each accession of crossbred, the accessions originating from different areas such as the SM 35 of Nusa Tenggara Barat and HS 49 from East Nusa Tenggara is also possible to have a genetic similarity with accessions from South Sulawesi, such as SP 8, SP 16, SP 33 and SP 38. the previous study (Salim, 2010) on the accession of the elder-accession states that accession HS 49 from NTT has a genetic similarity (89.6%) with the accession SP 38 from South Sulawesi, as well as the accession of NTB SM 35 with the accession SP 16 from South Sulawesi has a genetic similarity coefficient reached 92%.